2005
DOI: 10.1093/aje/kwj005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Intake and Risk of Osteoporotic Hip Fracture in Utah: An Effect Modified by Smoking Status

Abstract: The role of antioxidant intake in osteoporotic hip fracture risk is uncertain and may be modified by smoking. In the Utah Study of Nutrition and Bone Health, a statewide, population-based case-control study, the authors investigated whether antioxidant intake was associated with risk of osteoporotic hip fracture and whether this association was modified by smoking status. The analyses included data on 1,215 male and female cases aged > or = 50 years who incurred a hip fracture during 1997-2001 and 1,349 age- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 34 publications
10
136
1
Order By: Relevance
“…Similarly, epidemiological studies have provided evidence for the increased risk of bone fractures in patients with vitamin C deficiency as well as in smokers with insufficient intake of other antioxidants, such as vitamin E and selenium (6,8). The severity of antioxidant depletion and its relevance to the pathogenesis of multiple cell types and the ability of AA to induce differentiation of multipotent progenitor cells to osteoblasts, chondrocytes, cardiac myocytes, and dopaminergic neurons suggested that AA must be acting via other novel mechanisms to regulate cell differentiation at early stages and subsequent bone formation besides its well studied action to promote collagen synthesis/maturation and matrix protein interaction (14,15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, epidemiological studies have provided evidence for the increased risk of bone fractures in patients with vitamin C deficiency as well as in smokers with insufficient intake of other antioxidants, such as vitamin E and selenium (6,8). The severity of antioxidant depletion and its relevance to the pathogenesis of multiple cell types and the ability of AA to induce differentiation of multipotent progenitor cells to osteoblasts, chondrocytes, cardiac myocytes, and dopaminergic neurons suggested that AA must be acting via other novel mechanisms to regulate cell differentiation at early stages and subsequent bone formation besides its well studied action to promote collagen synthesis/maturation and matrix protein interaction (14,15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in humans founded that selenium status was inversely related to bone remodeling and positively correlated with BMD in post-menopausal women (88). A case-control study found selenium intake to be inversely associated with reduced risk of osteoporotic hip fracture (89). These effects can be explained by inhibiting oxidative stress, in fact, adequate selenium intake appears to play an essential role in osteoclast/osteoblast cell proliferation and differentiation enhancing osteoblastic differentiation by the reduction of free radicals (90).…”
Section: Seleniummentioning
confidence: 97%
“…some studies found that low vitamin C status in smokers significantly increased the risk of hip fracture, particularly where vitamin e intake was low 66,71 , although others have found no association 72 . Intervention studies show mixed results, which may be due to trial length.…”
Section: Calcificationmentioning
confidence: 99%
“…among the human studies, Maggio et al found that in women with osteoporosis, plasma levels of vitamin E were significantly lower 29 and a more recent investigation showed that in early postmenopausal women, a lower α-tocopherol/lipid ratio was associated with greater risk of osteoporosis and lower BMd 83 . despite this, Macdonald et al showed that increased dietary intake of vitamin e was inversely associated with BMd although the addition of intake from supplements removed this association 67 and a number of smaller studies have shown a detrimental association between vitamin e intake or serum levels and BMd or fracture risk, particularly among those with high oxidative stress, such as smokers 31,71,72 . In the only two human studies to consider other vitamin e isomers, hamidi et al showed that high serum γ-tocopherol and a low ratio of serum α-tocopherol to γ-tocopherol were associated with increased bone specific alkaline phosphatase, a marker for bone formation, although there was no association with urinary N-telopeptides, a marker for bone resorption 84 , while wolf et al found no association with BMD for serum α-or γ-tocopherol 42 .…”
Section: Calcificationmentioning
confidence: 99%